Hyperoside protects primary rat cortical neurons from neurotoxicity induced by amyloid beta-protein via the PI3K/Akt/Bad/Bcl(XL)-regulated mitochondrial apoptotic pathway - Zeng, Ke-Wu; Wang, Xue-Mei; Ko, Hyeonseok; Kwon, Hak Cheol; Cha, Jin Wook; Yang, Hyun Ok (ELSEVIER SCIENCE BV, 2011)
Amyloid beta-protein (A beta), which is deposited in neurons as neurofibrillary tangles, is known to exert cytotoxic effects by inducing mitochondrial dysfunction. Additionally, the PI3K/Akt-mediated interaction between Bad and Bcl(XL) plays an important role in maintaining mitochondrial integrity. However, the application of therapeutic drugs, especially natural products in Alzheimer's disease therapy via PI3K/Akt/Bad/Bcl(XL)-regulated mitochondrial apoptotic pathway has not aroused extensive attention. In the present study, we investigated the neuroprotective effects of hyperoside, a bioactive flavonoid compound from Hypericum perforatum, on A beta(25-35)-induced primary cultured cortical neurons, and also examined the potential cellular signaling mechanism for A beta detoxication. Our results showed that treatment with hyperoside significantly inhibited A beta(25-35)-induced cytotoxicity and apoptosis by reversing A beta-induced mitochondrial dysfunction, including mitochondrial membrane potential decrease, reactive oxygen species production, and mitochondrial release of cytochrome c. Further study indicated that hyperoside can activate the PI3K/Akt signaling pathway, resulting in inhibition of the interaction between Bad and Bcl(XL), without effects on the interaction between Bad and Bcl-2. Furthermore, hyperoside inhibited mitochondria-dependent downstream caspase-mediated apoptotic pathway, such as that involving caspase-9, caspase-3, and poly ADP-ribose polymerase (PARP). These results demonstrate that hyperoside can protect AB-induced primary cultured cortical neurons via PI3K/Akt/Bad/Bcl(XL)-regulated mitochondrial apoptotic pathway, and they raise the possibility that hyperoside could be developed into a clinically valuable treatment for Alzheimer's disease and other neuronal degenerative diseases associated with mitochondrial dysfunction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TERT-BUTYL HYDROPEROXIDE; ALZHEIMERS-DISEASE; HIPPOCAMPAL-NEURONS; HYDROGEN-PEROXIDE; CELL-SURVIVAL; DYSFUNCTION; AKT; ACTIVATION; TOXICITY; INJURY